Pengaruh Kebiasaan Merokok Dan Pola Makan Pasien Terhadap Kejadian Hipertensi Pada Pasien Rawat Inap Dirumah Sakit Bhayangkara Makassar - Andi Agustang; Imelda. H; Juli Tandibua; Surya Prihatini (Barongko: Jurnal Ilmu Kesehatan, 2026)
Hypertension can be defined as a medical condition or blood pressure in the arteries that is higher than normal. Blood pressure indicates the level of force exerted by blood on the surface of arterial blood vessels when blood is pumped by the heart. Smoking can also increase the risk of diabetes, heart attack, and stroke. Therefore, continuing to smoke while having high blood pressure is a very dangerous combination that will trigger diseases related to the heart and blood. Research objective: to determine the relationship between smoking habits and diet with the incidence of hypertension in inpatients at Bhayangkara Hospital Makassar. The type of research used was quantitative research with a cross-sectional design. The population in this study were all inpatients with hypertension at Bhayangkara Hospital Makassar. The research sample consisted of 38 respondents obtained using accidental sampling. Data collection was conducted using questionnaires and medical records. Data analysis was performed using univariate and bivariate analysis with the Chi-Square test at a significance level of α = 0.05. The results showed that there was a relationship between smoking habits and the incidence of hypertension with a p-value of 0.044 (p < 0.05). In addition, there was a relationship between diet and hypertension with a p-value of 0.046 (p < 0.05). Respondents who were moderate to heavy smokers and had poor diets tended to have a higher risk of hypertension. The conclusion of this study is that there is a significant relationship between smoking habits and diet with the incidence of hypertension in inpatients at Bhayangkara Hospital Makassar. Therefore, health promotion efforts are needed to raise public awareness about the dangers of smoking and the importance of implementing a healthy diet to prevent hypertension.